2020
DOI: 10.1111/vde.12857
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral sarolaner againstLynxacarus radovskyiin naturally infested cats

Abstract: Background Lynxacarus radovskyi is a fur mite of cats. Several classes of ectoparasiticides have shown success for treatment, including an isoxazoline. Objectives To evaluate the efficacy of a single oral dose of sarolaner for the treatment of L. radovskyi mites in naturally infested cats. Animals Fourteen adult cats (six males and eight females), naturally infested with L. radovskyi. Methods and materials Animals were randomized according to sex and average pretreatment mite count. The cats were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…However, although there is no indication in the package leaflet for the oral use of sarolaner in cats, it has already been used successfully for the treatment of feline demodicosis [ 16 ] and lynxacariosis [ 15 ], and the authors did not report any clinical or laboratory changes in the animals, as was the case in this study ( Table S1 )…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, although there is no indication in the package leaflet for the oral use of sarolaner in cats, it has already been used successfully for the treatment of feline demodicosis [ 16 ] and lynxacariosis [ 15 ], and the authors did not report any clinical or laboratory changes in the animals, as was the case in this study ( Table S1 )…”
Section: Discussionmentioning
confidence: 83%
“…The oral formulation of sarolaner is available globally and has proven to be effective against canine otodectic mange [14]. Furthermore, it has already been used successfully for the treatment Lynxacarus radovskyi [15] and Demodex spp. [16] in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Because the animals in the current study were isolated from other infested animals, the residual effect against reinfestations as described by Han et al (2016) could not be evaluated. Campos et al (2020) found that the sarolaner was effective in controlling L. radovskyi in domestic cats, showing >95% efficacy from day D+30 when combined with another isoxazoline. This finding is similar to that achieved by fluralaner administered orally (Han et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“… 39 The use of oral sarolaner was evaluated against lynxacariosis and otodectic mange and was also effective. 40 , 41 A spot-on formulation combining selamectin and sarolaner was successful for the therapy of otodectic mange after a single application. 42 In another study, the efficacy of the above formulation against ear mites was assessed and it reached 94.4% following 1 month of administration.…”
Section: Discussionmentioning
confidence: 99%